«UKRAINIAN DECAMERONE»: EROTICS IN EARLY MODERN UKRAINIAN LITERATURE - Shmyrko, Khrystyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
This scientific article attempts to identify the main elements and means of creating eroticism that define the subject as an artistic discourse. Based on the analysis of selected texts by Ukrainian modernist authors, whose plots became the basis for the TV series “Love Island,” an attempt is made to expand the erotic discourse in Ukrainian literature. The research methodology involved the use of a socio-historical approach, feminist and intermedial studies. The selected works are analyzed using the historical and literary method of interpreting a literary text with the identification of the main features and elements of eroticism. By outlining the socio-historical background of erotic discourse, the article reveals the lack of gradual development of the topic in society and literature due to its constant taboo. The culmination of the break in the trends of traditional coverage of the theme of love in the era of folklore was the arrival of European ideas - modernism stopped the stagnation of erotic discourse in literature and society. One of the main drivers that contributed to the development of erotic discourse was the women’s movement, which facilitated the transition from the objectivity of the female body to the subjectivity of the female personality. The analysis of the selected works allowed us to outline three concepts within which the elements and features of eroticism were considered: la femme fatale, freewill love, and love tragicomedy. The main elements that make up eroticism are the aesthetic background, the beauty of the body, and the sensual level. In addition, a close intertwining of eroticism with psychology is revealed, which often go along together to achieve the author’s goals in the works.